Self-management practices among children and adolescents presenting with type 1 diabetes attending selected health facilities in Nairobi city county - W. Mugo, Ann; S. Orago, Alloys S.; Gachau, Albert G. (International Journal Of Community Medicine And Public Health, 2024)
Background: Diabetes is a high prevalence non-communicable disease (NCD), with its highest burden in low- and middle-income countries. The International Diabetes Federation estimates that the global prevalence of diabetes is approximately 537 million people. By 2030, this figure is expected to rise to nearly 643 million, and by 2045, it is projected to reach 783 million. In sub-Saharan Africa, an estimated 24 million adults have diabetes, with a regional prevalence of 4.5%. Children with diabetes in this region often remain undiagnosed, and even if diagnosed, many lack access to essential services and resources such as insulin, syringes, and monitoring equipment, leading to avoidable deaths. Methods: The study design was a descriptive cross-sectional study. The study was conducted between September 2021 and September 2022 among children and adolescents with type 1 diabetes who attended selected facilities in Nairobi City County, Kenya. Qualitative and quantitative data were obtained using a self-administered semi-structured questionnaire, focus group discussions, and key informant interviews with the participants. The data was cleaned and then exported to SPSS V.23 for analysis. Results: The study investigated the demographic and socio-economic profiles of children and adolescents with type 1 diabetes in the study area, their level of knowledge regarding self-management practices, the self-management practices carried out by these respondents and explored the relationship between demographic and socio-economic factors, knowledge levels, and self-management practices among children and adolescents with T1D. Conclusions: The study findings will be of great importance for health professionals and policymakers in designing appropriate interventions to improve self-management practices among children with T1D.